2020
DOI: 10.3390/app10217587
|View full text |Cite
|
Sign up to set email alerts
|

Crack Width and Propagation in Recycled Coarse Aggregate Concrete Beams Reinforced with Steel Fibres

Abstract: Reducing the crack width is a vital feature for protecting rebars from corrosion. In this investigation, the impact of steel fibres (SFs) on the cracking of recycled coarse aggregate reinforced concrete (RCARC) beams was investigated. Twenty-seven reinforced concrete (RC) experimental samples (150 mm × 200 mm × 1500 mm) were manufactured. Shear rebars were considered with different spacings. Specimens were tested under a four-point flexural setup. Recycled coarse aggregate (RCA) from a destroyed building was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The crack evolution of beams could be divided into three stages during the loading process: (1) after the beam cracking, the cracks developed rapidly along the height of beam section and the number of cracks increased as the load increased (2) with the increase of load, the shear cracks appeared in the shear span of beam and the crack propagation rate in the pure bending section of beam was slowed down; (3) after the tensile reinforcement yielded, there were no new cracks emerged and the main cracks propagated rapidly, and the concrete in the compression zone was crushed until beam failed. It could be seen from Figure 4 that the crack pattern of the concrete beam with RFA replacement ratio of 100% was similar to that of ordinary concrete beam, and the cracks of SFRAC beam became fine and dense with the increase of steel fiber volume fraction, which is in agreement with the results found by Ghalehnovi (Ghalehnovi et al, 2020). For SFRAC beams, the crack spacing and crack numbers did not change significantly as the RA replacement ratios increased (Evangelista and Brito, 2017).…”
Section: Resultssupporting
confidence: 88%
“…The crack evolution of beams could be divided into three stages during the loading process: (1) after the beam cracking, the cracks developed rapidly along the height of beam section and the number of cracks increased as the load increased (2) with the increase of load, the shear cracks appeared in the shear span of beam and the crack propagation rate in the pure bending section of beam was slowed down; (3) after the tensile reinforcement yielded, there were no new cracks emerged and the main cracks propagated rapidly, and the concrete in the compression zone was crushed until beam failed. It could be seen from Figure 4 that the crack pattern of the concrete beam with RFA replacement ratio of 100% was similar to that of ordinary concrete beam, and the cracks of SFRAC beam became fine and dense with the increase of steel fiber volume fraction, which is in agreement with the results found by Ghalehnovi (Ghalehnovi et al, 2020). For SFRAC beams, the crack spacing and crack numbers did not change significantly as the RA replacement ratios increased (Evangelista and Brito, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Therefore, recycled coarse aggregates (RCA) and other waste materials aid in conserving natural resources and can be utilized to make concrete elements as a substitute for cement or natural coarse aggregates (NCA). In this regard, the structural performance of concrete members made from various recycled materials has been studied in a variety of ways 18–23 . Breccolotti and Materazzi 24 investigated the eccentrically loaded performance of RCA‐RC columns experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the structural performance of concrete members made from various recycled materials has been studied in a variety of ways. [18][19][20][21][22][23] Breccolotti and Materazzi 24 investigated the eccentrically loaded performance of RCA-RC columns experimentally and numerically. Also, the effect of concrete compressive strength on the performance of RCA concrete was measured experimentally, and it revealed that RCA had a larger scattering in the compressive resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many types of fibre reinforced concrete (FRC), including steel and synthetic materials, have been investigated to serve as a material that can partially or fully substitute for RC in structures [17][18][19][20][21][22]. In particular, steel fibre reinforced concrete (SFRC) is becoming increasingly used in structures because it has advantages over RC in terms of increasing cracking resistance and residual strength of cracked concrete due to the fibres bridging effect [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%